The - Buckley, Peter J. (Academic Press, 1994)
The recent developments in Eastern Europe and the former Soviet Union are providing Western businesses with new opportunities and challenges as a potentially huge new market emerges. While most Western firms are busy debating the impact of the EC and how to develop their strategies to handle a single European market of 223 million people, they are often unaware of the emergence of the enormous opportunities available in Eastern and Central Europe and the former Soviet Union with a market of 400-500 million consumers. This market is untapped in almost all sectors. Not only consumers, but also the state owned organizations, cooperatives and the emerging private enterprises want Western goods and technologies